Parallel and Distributed Computing, Applications and Technologies : 19th International Conference, PDCAT 2018, Jeju Island, South Korea, August 20-22, 2018, Revised Selected Papers /: 19th International Conference, PDCAT 2018, Jeju Island, South Korea, August 20-22, 2018, Revised Selected Papers. (2019) - Unknown
No abstract available